The sustainability of a sugarcane plantation in Brazil assessed by the eddy covariance fluxes of greenhouse gases - Cabral, Osvaldo M.R.; Freitas, Helber Custódio; Cuadra, Santiago Viana; de Andrade, Cristiano Alberto; Ramos, Nilza Patricia; Grutzmacher, Priscila; Galdos, Marcelo; Packer, Ana Paula Contador; da Rocha, Humberto Ribeiro; Rossi, Paulo (Agricultural and forest meteorology, 2020)
•This sugarcane agro-system was a carbon sink.•The NEE of CO2 fluxes (assimilation versus respiration) dominated the balances.•The N2O and CH4 emitted totals were offset by the C gain. The sustainability of sugarcane farming for biofuel has recently become a subject of debate, because its expansion may contribute significantly to global climate change mitigation. Here we report greenhouse gases (GHG) fluxes, measured by the eddy covariance method, from a commercial scale rain-fed sugarcane plantation representative of the leading bioethanol production area in southeast Brazil. The measurements covered two harvests, during which the field received nitrogen fertilization and trash was not removed. The cumulative fluxes for nitrous oxide (N2O) (62.4 ± 1.3 and 52.3 ± 1.8 g N2OCO2 eq. m−2 for the first and second years, respectively) and methane (CH4) (12.1 ± 1.7 and 10.4 ± 2.3 g CH4CO2 eq. m−2 for the first and second years, respectively) were minor sources to the atmosphere in comparison with the net ecosystem exchange (NEE) of carbon dioxide (CO2), whose sink dominated the balances (−7643. ± 129. and -4615. ± 124. g CO2 m−2 for the first and second years, respectively). Compared to the first year, the observed NEE in the second year decreased by 40%, as it covered the first re-growth from the stubble (ratoon) and exhibited a shorter growth cycle than the first year (304 versus 390 days). The second year also included the partial decomposition of the trash remaining on the soil after the first harvest (1581 ± 301 g CO2 m−2). The net ecosystem carbon balances (NECB), obtained as the cumulative fluxes of GHGs and the stalk dry biomass removed in the harvests (4923 ± 459 and 3929 ± 352 g CO2 m−2 for the first and second years, respectively) were -2646 ± 459 and -623 ± 352 g CO2 m−2 for the first and second years, respectively. Although the yields in stalk fresh weight (SFW) were representative of the region (9.9 and 8.2 kg SFW m−2, in the first and second year respectively) other factors caused a decrease of 76% in NECB, stressing the importance of the CO2 balance (assimilation versus respiration). Nevertheless, this sugarcane agro-system was an overall carbon sink with the N2O and CH4 emitted totals being offset by the net carbon gain. [Display omitted]